Analisis Pembelajaran Pendidikan Agama Islam dalam Membina Akhlak Siswa di SMA - Sa'adah, Laily Nur; Rindaningsih, Ida (MODELING: Jurnal Program Studi PGMI, 2024)
The purpose of this study is to describe the analysis of Islamic religious education learning. The research method used is qualitative research. Data collection techniques include observation, interviews and documentation. The three steps of data analysis used are data reduction, data presentation and drawing conclusions. The results of the study indicate that in Islamic Religious Education learning there are 3 steps that must be carried out, namely learning planning, learning implementation and learning evaluation, in fostering student morals, the right strategy is carried out in Islamic Religious Education learning, namely the Cooperative Learning strategy. The form of student moral development activities carried out by the school is student moral development through intracurricular activities and student moral development through extracurricular activities. Student moral development through intracurricular activities includes habituation activities, and exemplary activities. Student moral development through extracurricular activities includes congregational Dhuha prayer activities, congregational Dhuhur prayer activities and congregational Friday prayer activities.